Aligning IT Strategy with Operational Performance: A Case Study of the Semarang-Demak Toll Road Project - Nurcholis Kurniawan; Dessy Isfianadewi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to provide an in-depth understanding of how Information Technology (IT) strategies are aligned with operational performance at PT PP Semarang Demak (PPSD), specifically regarding the implementation of the RFID-based Lajur Otomatis (LOS) system. Motivated by the need to manage traffic fluctuations and enhance service efficiency, the research employs a qualitative case study approach. Data were collected through in-depth interviews with key stakeholders from the Engineering, Operations, and Finance divisions, supplemented by direct field observations conducted between February and June 2024. The findings indicate that while the IT strategy is highly congruent with operational needs significantly reducing congestion and accelerating transaction speeds the integration process is hindered by technical and organizational barriers. Key challenges identified include limited human resource competency, environmental disruptions, and the financial risk of technology mismatch. The study concludes that sustainable alignment requires more than technical adoption; it demands rigorous validation mechanisms, such as Proof of Concept (PoC), and continuous investment in human capital. These insights offer valuable strategic implications for the construction and infrastructure sector regarding the effective management of digital transformation.